Online Purchasing Habits of the Students in the Era of the COVID-19 Pandemic - Pikl, Lorena; Štefić, Petra; Treska, Lea; Gregurec, Iva (45th International Conference on Organizational Science Development: Organization and the Longevity Society, Conference Proceedings, 2026)
This paper investigates the impact of the COVID-19 pandemic on online purchasing habits among students at the Faculty of Organization and Informatics, University of Zagreb. The quantitative research, conducted via online survey, aimed to analyse whether and to what extent the pandemic altered students’ prior online purchasing behaviour. Using a T-test, differences in perceived security, price sensitivity, time-saving aspects, and overall attitudes toward online shopping before and during the pandemic were assessed. The results indicate no statistically significant shift in students’ perception of safety regarding online purchases. However, statistically significant differences were identified in price sensitivity, time-saving perceptions, and attitudes toward online purchasing before the pandemic. These findings confirm the main hypotheses, indicating a significant difference in students' online purchasing habits before and during the COVID-19 pandemic. Additionally, the study provides valuable insights into pandemic-induced changes in student behaviour and offers practical implications for marketers and retailers to enhance the efficiency of online shopping and adapt their strategies to evolving consumer needs and preferences, particularly among students.